Thermo-economic assessment of metallic high-temperature latent heat storage system - Ray, Alok Kumar; Vashisht, Sagar; Rakshit, Dibakar; Ravi Kumar, K.; Gurgenci, Hal (Frontiers in Thermal Engineering, 2025)
The promising prospects of high-temperature latent heat storage (HT-LHS) systems are accentuated by their advantages, including significant energy storage density, superior energetic efficiency, quasi-isothermal functionality, and seamless integration with renewable energy systems such as 3rd Gen Concentrated Solar Plant and Thermophotovoltaic systems. This study evaluates the thermo-economic performance of a proposed HT-LHS system having silicon as phase change material (PCM). A single thermal cell and a complete LHS system (consisting of several thermal cells) integrated with the supercritical CO2 cycle are considered for the thermal and economic analyses, respectively. Furthermore, the charging performance of an equivalent thermal cell is compared with a specific Li-ion cell. Notably, a single thermal cell’s gravimetric and volumetric energy densities surpass those of the specific Li-ion cell by approximately fourfold. Moreover, the charging time of the equivalent thermal cell, with minimal heat flow, is notably shorter than that of the Li-ion cell with comparable capacity. In terms of the levelized cost of electricity (LCoE), the HT-LHS technology demonstrates a significantly lower price of 9.547 Rs/kWh when storing 200 MWh of energy. Sensitivity analysis of LCoE reveals the opposite effect of loan repayment years (LOY) compared to other economic parameters. LCoE varies by 23.1%,16.43%,14.4%, and 8.06% by changing Return on equity (ROE), interest rate on the loan (IOL), Operation and maintenance cost, and discount rate from −40% to 40%.